如何证明 (sin(a)-cos(b))/(sin(b)-cos(a))-(sin(b)-cos(…?
2024-11-22 阅读 18
要证明这个表达式,我们可以尝试将其化简。首先,将分子和分母分别展开:
分子:sin(a) - cos(b)
分母:sin(b) - cos(a)
然后,将分子和分母分别展开:
(sin(a) - cos(b))/(sin(b) - cos(a)) = (sin(a)/sin(b) - cos(b)/sin(b)) / (sin(b)/sin(b) - cos(a)/sin(b))
继续化简:
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cos(a)/sin(b))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (sin(b)/sin(b) - cos(a)/sin(b))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cos(a)/sin(b))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a) - cos(b))/sin(b) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a)/sin(b) - cos(b)/sin(b)) / (1 - cot(a))
= (sin(a
更新于 2024年11月24日